Nash bargaining and policy impact in emerging ISP-CP relationships. (29th October 2020) - Garmani, Hamid; Omar, Driss Ait; Amrani, Mohamed El; Baslam, Mohamed; Jourhmane, Mostafa
This paper studies a non-neutral network where internet service providers (ISPs) charge content providers (CPs) for content delivery. We investigate the mutual interaction among ISP and CP in two cases: 1) competitive case, where the ISP charge CP for delivering content to end-users; 2) cooperative case, where the two providers (CP, ISP) jointly optimise their strategies, to maximise their aggregate profits. We formulate the interactions between multiple ISPs (multiple CPs) as a non-cooperative game. We utilise bargaining games to analyse how the side payment between CP and ISP is determined. Also, the existence and uniqueness of the Nash equilibrium are proven. Based on the best response dynamics method, we propose a distributed iterative algorithm, starting from any initial strategies vector and converge to that Nash equilibrium. Finally, through extensive simulations, it has been verified that cooperation is the best choice for three entities, i.e., ISP, CP, and end-users.